ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN BPJS MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS DAN QUALITY FUNCTION DEPLOYMENT - Simanjuntak, Risma A.; Purwasih, Yenni (Proceeding SENDI_U, 2017)
Health is one of the most important necessity in society. That is why so many service industries in health sector, both governmental and private. It has the impact for the bussiness competition between the hospitals as the service actor. For that reason, every hospitals need to increase the service quality to feed the patients’ satisfaction. Base on the result of the initial observation such as the interview with some BPJS’ patients, and by observing in social media, the result shows that more than 20 comments tell that they have not satisfied yet with the BPJS’ service in RSUD XXX, and still many complaints to BPJS’s service. The complaints such as the doctor didn’t want to hear the patient’s grievance; the advance medical tool such as rontgen still inadequate, and the last is the medicine in the pharmacy is still not complete. For those reasons, the service quality measurement is needed to be done to know how to improve the BPJS’ service to become as patient’s wishes using Importance Performance Analysis and QFD (Quality Function Deployment). Importance Performance Analysis is the most effective method to analyze the patients’ satisfaction with their expectation, and QFD is used to contrive the service quality improvement correspond with the customer’s requirements and also the capability of the hospital’s management. The results of the research show that from 35 service quality attributes, there are 9 priority attributes that should be fixed by the hospital. Service attribute that has the highest priority to be fixed is the completeness of medicine in pharmacy for BPJS’ patients with the precentage 16,35%. After that, technical actions with the highest priority is the evaluation of nurse and doctor performance (0,282), and make the clear S.O.P for the health workers (0,242). Key words : Quality,Importance Performance Analysis , Quality FunctionDeployment (QFD).